GLOBAL CULTURE, CULTURAL HYBRIDITY, AND INTRA-SENTENTIAL CODE-MIXING ON DEVINA HERMAWAN'S YOUTUBE CHANNEL - Atina Firdausa Qisthi; Sigit Ricahyono; Tri Wahyuni Chasanatun (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
This study identifies the types of Indonesian-English code-mixing in YouTube videos of Devina Hermawan in reflecting global culture and cultural hybridity. In examining the types of intra-sentential code-mixing, the researchers adopt Muysken (2000) that there are three sub-types i.e. insertion, alternation, and congruent lexicalization. The data are collected online from “Masakan Indonesia: Indonesian Cuisine” playlist on Devina Hermawan’s YouTube channel. They are transcribed and selected based on the types. The results show that there are 159 utterances containing Indonesian-English code-mixing in five selected videos. Further, the utterances categorized as insertional type become the most frequent cases, 86 utterances (54%), followed by congruent lexicalization type in the second place, 65 utterances (41%). The utterances which categorized as alternational type are less frequently found in the videos, 8 utterances (5%). In this case, hybridization in language on the level of individual languages influence the phenomenon of code-mixing. Overall, the results of this study provide the analysis of types of code-mixing, which the texts under investigation, reflect the current global culture which is cultural hybridity.